2015
DOI: 10.1002/chem.201501644
|View full text |Cite
|
Sign up to set email alerts
|

A Family of 12‐Azametallacrown‐4 Structural Motif with Heterometallic MnIII‐Ln‐MnIII‐Ln (Ln=Dy, Er, Yb, Tb, Y) Alternate Arrangement and Single‐Molecule Magnet Behavior

Abstract: Mixed 3d-4f 12-azametallacrown-4 complexes, [Mn2 Ln2 (OH)2 (hppt)4 (OAc)2 (DMF)2 ]⋅2 DMF⋅H2 O [Ln=Dy (1), Er (2), Yb (3), Tb (4) and Y (5), H2 hppt=3-(2-hydroxyphenyl)-5-(pyrazin-2-yl)-1,2,4-triazole)], were synthesized by reactions of H2 hppt with Mn(OAc)2 ⋅4 H2 O and Ln(NO3 )3 ⋅6 H2 O. This is the first 3d-4f azametallacrown family to incorporate Ln ions into the ring sets. These isostructural complexes exhibit alternating arrangements of two Mn and two Ln ions in the rings with each pair of metal centers bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Therefore, it is one of the challenges to synthesize lanthanide-containing complexes through choosing triazole-based ligands. Based on our previous study, [14,23] herein, we reported three new heterometallic 2p-4f complexes [Na 2 {Ln 4 (μ 3 -OH) 2 (ppt) 4 (Hppt) 2 (OAc) 2 }(DMF) 4 ] (1 • 2.5H 2 O, Ln = Dy; 2 • 2H 2 O, Ln = Er; 3, Ln = Yb) with the presence of multiple metal rings using a rigid, unsymmetrical triazole-bridge ligand with phenol and pyrazine groups. In this manuscript, we reported the syntheses, crystal structures and magnetic properties of these three complexes.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, it is one of the challenges to synthesize lanthanide-containing complexes through choosing triazole-based ligands. Based on our previous study, [14,23] herein, we reported three new heterometallic 2p-4f complexes [Na 2 {Ln 4 (μ 3 -OH) 2 (ppt) 4 (Hppt) 2 (OAc) 2 }(DMF) 4 ] (1 • 2.5H 2 O, Ln = Dy; 2 • 2H 2 O, Ln = Er; 3, Ln = Yb) with the presence of multiple metal rings using a rigid, unsymmetrical triazole-bridge ligand with phenol and pyrazine groups. In this manuscript, we reported the syntheses, crystal structures and magnetic properties of these three complexes.…”
Section: Introductionmentioning
confidence: 99%
“…We reported the first family of heterometallic Mn/Ln azametallacrowns, and discussed their synthesis, structures and SMM behaviour. [14] These isostructural azametallacrowns display Mn/Ln ions alternating arrangements.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations